Multisystem Inflammatory Syndrome and Autoimmune Diseases Following COVID-19: Molecular Mechanisms and Therapeutic Opportunities - Hosseini, Parastoo; Fallahi, Mohammad Sadegh; Erabi, Gisou; Pakdin, Majid; Zarezadeh, Seyed Mahdi; Faridzadeh, Arezoo; Entezari, Sarina; Ansari, Arina; Poudineh, Mohadeseh; Deravi, Niloofar (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) has led to huge concern worldwide. Some SARS-CoV-2 infected patients may experience post-COVID-19 complications such as multisystem inflammatory syndrome, defined by symptoms, including fever, elevated inflammatory markers (such as elevation of C reactive protein (CRP), erythrocyte sedimentation rate, fibrinogen, procalcitonin test, D-dimer, ferritin, lactate dehydrogenase or IL-6, presence of neutrophilia, lymphopenia, decreased albumin, and multiple organ dysfunction). Post-COVID-19 complications may also manifest as autoimmune diseases such as Guillain-Barré syndrome and systemic lupus erythematosus. Signaling disor-ders, increased inflammatory cytokines secretion, corticosteroids use to treat COVID-19 patients, or impaired immune responses are suggested causes of autoimmune diseases in these patients. In this review, we discuss the molecular and pathophysiological mechanisms and therapeutic oppor-tunities for multisystem inflammatory syndrome and autoimmune diseases following SARS-CoV-2 infection with the aim to provide a clear view for health care providers and researchers.